2011
DOI: 10.1183/09031936.00190410
|View full text |Cite
|
Sign up to set email alerts
|

Increased lung neutrophil apoptosis and inflammation resolution in nonresponding pneumonia

Abstract: Neutrophil activation state and its relationship with an inflammatory environment in community-acquired pneumonia (CAP) remain insufficiently elucidated. We aimed to evaluate the neutrophil apoptosis and cytokine pattern in CAP patients after 72 h of treatment, and their impact on infection resolution.Apoptosis of blood and bronchoalveolar lavage (BAL) neutrophils was measured in nonresponding CAP (NCAP), in responding CAP (blood only) and in patients without infection (control). Proinflammatory (interleukin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
(33 reference statements)
3
33
0
Order By: Relevance
“…Studies in mice have shown that survival is associated with a strong inflammatory response early in the course of infection and rapid bacterial clearance [2]. In both mice and humans, regulation of this inflammatory response in pneumonia is dependent on complex interactions between immune cells and pro-and anti-inflammatory cytokines [2][3][4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in mice have shown that survival is associated with a strong inflammatory response early in the course of infection and rapid bacterial clearance [2]. In both mice and humans, regulation of this inflammatory response in pneumonia is dependent on complex interactions between immune cells and pro-and anti-inflammatory cytokines [2][3][4].…”
mentioning
confidence: 99%
“…Several cytokines have been studied in relation to severity, aetiology and outcome of CAP [4][5][6][7][8][9][10][11][12][13][14][15]. Although the number of cytokines identified in the immunopathogenesis of CAP has increased considerably over the years, studies remain focused on well-known cytokines of the innate immune response, including interleukin (IL)-6, IL-10, IL-8, IL-1b and tumour necrosis factor (TNF)-a. IL-17A and IL-22, which belong to the novel T-helper (Th) 17 subset, have also been implicated in CAP [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In community-acquired pneumonia and bronchiectasis the delayed apoptotic activity of neutrophils is observed not only in the blood, but also in the sputum and broncho-alveolar lavage [61,66]. The extended lifespan of neutrophils in the locus of infection is an adverse factor contributing to an ineffective removal of pathogens [10,46].…”
Section: Role Of Neutrophil Apoptosis In the Resolution Of Inflammationmentioning
confidence: 99%
“…[6][7][8] Appropriately producing cytokines in location play a role in inhibition and elimination of primary infection, but an excessive systemic and pulmonary inflammatory response in patients with severe CAP may contribute to injuries to the lung and other organs. This leads to sepsis, lung injury, and ARDS and is associated with poor prognosis and high mortality.…”
Section: Introductionmentioning
confidence: 99%